Réponses

2017-01-12T16:45:36+01:00
Salut
P(0)=0.5    P'(0)=0    P(1)=0      P'(1)=0
P(x)=ax^3+bx^2+cx+d      P'(x)=3ax^2+bx+c
P(0)=a*0^3+b*0^2+c*0+d=0.5          d=-0.5
P'(0)=3a*0^2+2b*0+c=0                    c=0
P(1)=a*1^3+b*1^2+d=0        a+b+d=0    d'ou  a+b=-0.5
P'(1)=3a*1^2+2b=0                                          3a+2b=0
on resouds le systeme
a+b=-0.5    (1)
3a+2b=0    (2)

(1)*-2  -2a-2b=1
           3a+2b=0
         ---------------
             a=1
(1)  1+b=-0.5    b=-1.5
P(x)=x^3-1.5x^2+0.5